Assessing the role of Agricultural Development Programme in the Implementation of Fadama III Project to Empower Adult Users in Edo State, Nigeria - ERHARUYI, Richard Nosakhare; UGWOEGBU, Ifeanyin Theodore; ADEBOLA, Helen Ebunoluwa (Ilorin Journal of Education, 2023)
The Study was carried out to assess the role of Agricultural Development Programme (ADP) in the implementation of Fadama III project in Edo State. The purpose of this study was to assess the role of Edo State ADP in the implementation of Fadama III project in the State through its unit; Edo State Fadama Coordinating Office (EDSFCO). The study was guided by three research questions. A descriptive survey research design was adopted for the study. The population of the study consisted of a total of 1,175 registered Fadama User Groups (FUGs) in Edo State and all Edo State ADP staff comprising; agricultural extension workers and Edo State Fadama Coordination Office (EDSFCO) staff. The study also adopted empowerment theory by Julian Rappaport. Sample size of 341 respondents was selected through multistage sampling techniques. The data for this study was obtained using a questionnaire. It was validated by two lecturers in the Department of Adult and Non–Formal Education, University of Benin. The test-retest method of estimating reliability was used to ascertain the reliability coefficient of the instrument. Data were analyzed using mean scores. The findings of the study revealed that EDSFCO carried out various training for farmers in capacity building in terms of skill acquisition in fishing, crop preservation and pest management. Based on the findings, it was recommended among others that Agricultural Development Programme (ADP) should be equipped in order to carry out regular trainings and sensitization workshops on crops, fisheries, agro forestry and livestock in the State.